Bioethical Decision Making and Argumentation Foreword - Serna, Pedro (Bioethical decision making and argumentation, 2020)
This book clarifies the meaning of the most important and pervasive concepts and tools in bioethical argumentation (principles, values, dignity, rights, duties, deliberation, prudence) and assesses the methodological suitability of the main methods for clinical decision-making and argumentation. The first part of the book is devoted to the most developed or promising approaches regarding bioethical argumentation, namely those based on principles, values and human rights. The authors then continue to deal with the contributions and shortcomings of these approaches and suggest further developments by means of substantive and procedural elements and concepts from practical philosophy, normative systems theory, theory of action, human rights and legal argumentation. Furthermore, new models of biomedical and health care decision-making, which overcome the aforementioned criticism and stress the relevance of the argumentative responsibility, and some legal and institutional reflection on international bioethics committees, are included.
Keywords: argumentation in bioethics committees; bioethical argumentation; bioethical decision making process; bioethical decision-making; WOS(2)